2021
DOI: 10.1177/10778012211032699
|View full text |Cite
|
Sign up to set email alerts
|

#MeToo on the Canadian Prairies: Raising Awareness of Sexual Assaults and Mental Health in Women Abused by Intimate Partners

Abstract: Studies of intimate partner sexual assault (IPSA) and its effects on mental health are limited. This secondary data analysis examines IPSA, a history of child sexual abuse, depression, trauma, mental distress and quality of life in 665 Canadian women, 41% of whom had been sexually assaulted by intimate partners; 53% were sexually abused as children. Women who had experienced any IPSA had significantly higher scores on all Composite Abuse subscales (IPV), mental distress (SCL-10), and depression (CES-D-10). PTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…The current secondary mixed-methods analysis provides in-depth, contextual information about the concerns faced by Canadian Indigenous women abused by their intimate partners. The results highlight the severity of their partner’s abusive behavior, including intimate partner sexual abuse (Tutty et al, 2023). It places their partner’s abusive behavior in the context of the women’s lives by exploring their backgrounds and current life circumstances, confirming the intersecting impacts of colonization, systemic oppression, and racism in their lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current secondary mixed-methods analysis provides in-depth, contextual information about the concerns faced by Canadian Indigenous women abused by their intimate partners. The results highlight the severity of their partner’s abusive behavior, including intimate partner sexual abuse (Tutty et al, 2023). It places their partner’s abusive behavior in the context of the women’s lives by exploring their backgrounds and current life circumstances, confirming the intersecting impacts of colonization, systemic oppression, and racism in their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Partner sexual assault is an under-researched area (Bagwell-Grey et al, 2015; Logan et al, 2015; Tutty et al, 2023). Guggisberg (2019) suggested that Indigenous women may face even greater confusion given the legacy of colonization and intergenerational transmission of abuse, which also includes sexual assaults.…”
Section: Discussionmentioning
confidence: 99%
“…15 The Canadian prairie provinces (Alberta, Saskatchewan and Manitoba) report higher violence against women than the rest of Canada. 19 Findings in these provinces highlight the harm violence has on women's lives 20 and emphasise the importance of considering women's contexts and intersecting identities (eg, cultural background, gender, disability) when developing person-centred interventions. [20][21][22][23] The COVID-19 pandemic has dramatically affected the health of many individuals, especially among people already burdened by social and structural health inequities.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…19 Findings in these provinces highlight the harm violence has on women's lives 20 and emphasise the importance of considering women's contexts and intersecting identities (eg, cultural background, gender, disability) when developing person-centred interventions. [20][21][22][23] The COVID-19 pandemic has dramatically affected the health of many individuals, especially among people already burdened by social and structural health inequities. 24 The pandemic also exacerbated mental health symptoms in many groups.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Recent qualitative research on the ‘invisible impacts’ of IPSV (Tarzia, 2021a) supports this argument, suggesting that it is a combination of betrayal and loss of trust, the unique sexualised nature of the violence and its dehumanising aspects, and the lingering impact on future relationships and women’s sense of sexual wellbeing that set IPSV aside from other forms of violence in relationships. Other researchers have also attempted to disentangle IPSV from other forms of violence (Jeffrey & Barata, 2021; Tutty & Nixon, 2021; Wright et al, 2021), however, there is still a long way to go before we truly understand this complex and hidden phenomenon.…”
Section: Introductionmentioning
confidence: 99%